PEREMPUAN DI MEJA MAKAN - Sari, Nurima; Indrayuda, Indrayuda (SENDRATASIK UNP, 2019)
Abstract The creation of the dance "Women at the Dining Table" aims to create a creative dance and express an idea of cultivation that departs from the today's issue of women's ethics at dining table. The creation of this dance begins by determining the type of dance object, the object of claim and the place of performance. The instruments used in the creation of dance are the time of the dance target, the production cost of the dance, the concept of cultivation and the process of cultivation. This dance entitled "Women in the Dining Table" is a dramatic type of dance with representational symbolic forms. The dance "Women at the Dining Table" is the artwork inspired by the ethics of todays’ women at the dining table. Today's eating ethics has not been noticed by women like Minangkabau saying is "sumbang makan". Eating ethics that are not good are caused by the influence and development of the era but as large as anything and as strong as the influence and development of the era, as Minangkabau women must reveal good eating ethics. The dance "Women at the Dining Table" is a dramatic dance with representational symbolic forms that are manifested through motion, stage, makeup, fashion, lighting, and music. Keywords: women at dinner table